Pengaruh Brand Image, Store Atmosphere, Product Quality dan Service Quality terhadap Minat Beli Ulang (Studi Kasus Pada Pelanggan Mie Gacoan Yogyakarta) - Ambar Lukitaningsih; Nonik Kusuma Ningrum; Farid Alif Muttaqin (Universitas Batanghari Jambi, 2023)
This study aims to determine how much influence Brand Image, Store Atmosphere, Product Quality and Service Quality have on Repurchase Intention. The population in this study were consumers from the Mie Gacoan restaurant in Yogyakarta. The sample in this study used a purposive sample. Data collection used a survey with the help of Google form using a Likert scale with an assessment of 1 (strongly disagree) to 5 (strongly agree). Processing the data in this study using multiple linear regression analysis. The results of this study state that Brand Image has a positive and significant influence on Repurchase Intention with a significance value (0.032 <0.05), Store Atmosphere has a positive and significant influence on Repurchase Intention with a significance value (0.017 <0.05), Product Quality has no significant effect on Repurchase Intention with a significance value (0.480 > 0.05), Service Quality has no significant effect on Repurchase Intention with a significance value (0.782 > 0.05).